Antimicrobial Activity of Michelia champaca - Elizabeth, K.M.; Jaya Lakshmi, Y.A.S. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of Michelia champaca was assessed against certain human pathogenic microorganisms by disc diffusion method. The crude aqueous extract, cold methanol extract, methanol distillate and residual extracts of flowers were used in the present study. The crude extract showed largest zone of inhibition towards Rhizopus species, i.e., 17 mm indicating that this extract was highly effective to this organism. E. coli showed 22.5 mm zone of inhibition to cold methanol extract of M. champaca flower. S. aureus and M. luteus were highly sensitive to distilled methanol forming 20 mm zone. The residual extract was strongly inhibitory towards S. aureus as it formed 26.5 mm zone and least inhibitory to S. typhimurium as it showed 7 mm zone. The MICs of residual extract ranged between 100-800 μg/mL, S. aureus with lowest and B. subtilis and Y. enterocolitica with highest MIC values indicating that S. aureus was strongly inhibited by the residual extract and B. subtilis and Y. enterocolitica were least sensitive to this extract. There was inhibition of amylase and protease production by methanol residual extract of this plant. The umber of colony forming units of the air microbial flora was reduced by 88% in 15 min following the spray of residual extract. These results indicate that this floral methanol extract acted as a broad spectrum antimicrobial agent and as it was a very fragrant extract, it can be used as antimicrobial deodorant, antimicrobial perfume and in operation theatres.